Formação de professores de matemática da educação superior e as tecnologias digitais: aspectos do conhecimento revelados no contexto de uma comunidade de prática online - Richit, Andriceli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The formation of the Higher Education Professor is discussed within the continuum perspective. Current research involved Math Professors in Brazil and abroad within a formation context and aimed at evidencing and understanding the pedagogical, technological, mathematical, cultural and social aspects of Math Professors within the context of an Online Practice Community. Current research was foregrounded by the question: Which aspects of knowledge emerge in the case of a Higher Education Math professor of an Online Practice Community? Discussion occurs within the qualitative perspective of research, whilst data are retrieved from an online extension course (Modules I, II and III) using Moodle Platform as a base for formation practice developed by synchronic and a-synchronic tools. In the extension course, the capacity of Digital Technologies was discussed within an approach for the concepts of Higher Education Mathematics, specifically Differential and Integral Calculus, Analytic Geometry and Linear Algebra. Further, the manner professors involved developed exploratory and investigative activities related to the disciplines above with the GeoGebra software. Data constituted by elements of Content Analysis, which were related to Chats, Forums, Reviews, Reflexive Memoirs, Final Lesson Plan, Admission Cards, Questionnaire and Course Assessment Card, were analyzed. Four categories developed from data analysis: (1) theoretical-methodological aspects of knowledge of the Higher Education Math Professor within the context of ICTs; (2) didactic-pedagogical, social and cultural aspects of ICTs; (3) epistemological aspects of mathematical concepts; and (4) cultural and political-pedagogical aspects of Math courses. Categories were analyzed by the theories of Practice Communities, TPACK and the Formation of Higher Education professors, and indicate understanding on the investigated object. Current investigation enhanced the capacity of Online Practice ...

A pesquisa desenvolvida tomou por objeto de estudo a formação do professor da Educação Superior na perspectiva do continuum. Para tanto, engajou professores de Matemática da Educação Superior do Brasil e do Exterior em um contexto formativo e objetivou evidenciar e compreender os aspectos pedagógicos, tecnológicos, matemáticos, culturais e sociais manifestados por professores de Matemática da Educação Superior no contexto de uma Comunidade de Prática Online. Desenvolvemos esta investigação norteadas pela questão: Que aspectos emergem do conhecimento do professor de Matemática da Educação Superior em uma Comunidade de Prática Online? Visando compreensões para a interrogação delineada, guiamo-nos segundo a perspectiva qualitativa de pesquisa e constituímos dados a partir de um Curso de Extensão Online (Módulos I, II e III), que utilizou a Plataforma Moodle como suporte à prática formativa, desenvolvida por meio de ferramentas síncronas e assíncronas. Discutimos, no contexto do Curso de Extensão, as potencialidades das Tecnologias Digitais na abordagem de conceitos de Matemática da Educação Superior, em específico de Cálculo Diferencial e Integral, Geometria Analítica e Álgebra Linear, bem como os docentes engajados desenvolveram atividades exploratório-investigativas relacionadas a conceitos das referidas disciplinas no software GeoGebra. Assim, analisamos os dados constituídos segundo alguns elementos da Análise de Conteúdo e relacionados aos: Chats, Fóruns, Resenhas, Memoriais Reflexivos, Plano Final de Aula, Fichas de Inscrição, Questionário e Ficha de Avaliação do Curso. Da análise dos dados, emergiram quatro categorias: (1) aspectos teórico-metodológicos do conhecimento do professor de Matemática da Educação Superior no contexto das TIC; (2) aspectos didático-pedagógicos, sociais e culturais das TIC; (3) aspectos epistemológicos de conceitos matemáticos; e (4) aspectos culturais e...
Keywords: Teachers, Training of; Professores - Formação; Matemática; Ensino superior; Comunidades de prática; Tecnologias de informação e comunicação